Bedding plane-embedded augmented virtual internal bonds for fracture propagation simulation in shale. Issue 3 (March 2021) - Liu, Zihan; Zhang, Zhennan; Ghassemi, Ahmad
Highlights: Bedding plane is embedded into the constitutive model of augmented virtual internal bond. The BP-embedded AVIB can represent various Poisson ratio of rock. The BP-embedded AVIB can simulate the fracture propagation in transverse isotropic rock. Abstract: To effectively simulate the fracture propagation in shale, the bedding plane (BP) effect is incorporated into the augmented virtual internal bond (AVIB) constitutive relation through BP tensor. Comparing the BP-embedded AVIB with the theory of transverse isotropy, it is found the approach can represent the anisotropic properties induced by parallel BPs. Through the simulation example, it is found that this method can simulate the stiffness anisotropy of shale and can represent the effect of BPs on hydraulic fracture propagation direction. Compared with the BP-embedded virtual internal bond (VIB), this method can account for the various Poisson's ratio. It provides a feasible approach to simulate the fracture propagation in shale.